Foreign-Trained Dentists in the United States: Challenges and Opportunities - Sergio Varela Kellesarian (MDPI AG, 2018)
The aim of the present study is to review the licensing process and challenges faced by foreign-trained dentists in United States (U.S.), and how incorporating foreign-trained dentists in the dental workforce in the U.S. impacts the population’s dental care. Foreign-trained dentists must complete additional training in a Commission of Dental Accreditation recognized program offered by a U.S. dental school in order to be eligible for licensing. Foreign-trained dentists interested in seeking employment in the U.S. face numerous challenges, including stringent admission processes, high tuition costs, immigration barriers and cultural differences. Opening the U.S. dental profession to foreign-trained dentists provides several advantages, such as increasing the diversity of dentists in the U.S., expanding access to underrepresented communities, and enhancing the expertise of the profession. Foreign-trained dentists are an important resource for a U.S. government seeking to build the human capital base and make the most of global trade opportunities through a “brain gain”. Increasing the diversity in the dental profession to match the general U.S. population might improve access to dental care for minorities and poor Americans, reducing disparities in dental care.